CLR‐4, a novel conserved transcription factor for cellulase gene expression in ascomycete fungi. Issue 2 (25th November 2018) - Liu, Qian; Li, Jingen; Gao, Ranran; Li, Jinyang; Ma, Guoli; Tian, Chaoguang
Summary: Fungal degradation of lignocellulosic biomass requires various (hemi‐)cellulases and is an important part of the natural carbon cycle. Although induction of cellulases has been described for some saprobic filamentous fungi, the regulation of cellulase transcription is complex and many aspects are still poorly understood. Here, we identified and characterized the novel cellulase regulation factor NcCLR‐4 in Neurospora crassa and its ortholog MtCLR‐4 in Myceliophthora thermophila . Deletion of CLR‐4 resulted in similarly defective cellulolytic enzyme production and activities. Transcriptome analyses of Δ Ncclr‐4 /Δ Mtclr‐4 revealed the down‐regulation of genes encoding (hemi‐)cellulases and pivotal regulators ( clr‐1, clr‐2 and xyr‐1 ) and key genes in the cAMP signaling pathway such as adenylate cyclase Nccr‐1 . Intracellular cAMP levels were markedly lower in Δ Ncclr‐4 /Δ Mtclr‐4 than in wild‐type during cellulose utilization. In electrophoretic mobility shift (EMSA) and DNase I footprinting assays, NcCLR‐4/MtCLR‐4 can directly bound to the promoters of Nccr‐1/Mtcr‐1 (encoding adenylyl cyclase). EMSAs also demonstrated that NcCLR‐4/MtCLR‐4 could directly bound to clr‐1 (encoding a key cellulase regulator), Mtclr‐2 and Mtxyr‐1 (encoding biomass deconstruction regulators). These findings about the novel cellulase expression regulators NcCLR‐4 and MtCLR‐4 enrich our understanding of how cellulose degradation is regulated and provide new targets for engineering fungi to deconstruct plant biomass in biorefineries. Abstract : Clr4, a novel conserved cellulase regulator in Neurosproa crassa and Myceliophthora thermophila was identified and functionally chararacterized. Clr4 activates cellulase gene expression through direct regulation of the major ligonocellulase regulators clr1/clr2/xyr‐1 as well as via cr‐1, which is a key component of cAMP pathway. The findings reported here may prove helpful for industrial strain engineering for cellulase production and thus reduce the cost of biofuel production.